ANALISIS PERBANDINGAN KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE ADDED (STUDI KOMPARATIF BANK MUAMALAT TBK DAN BANK COMMONWEALTH INDONESIA TBK, PERIODE 2010-2012) - RURIANA NINGSIH, EVA Ruriana (Jurnal Akuntansi AKUNESA, 2014)
Economic growth is essentially influenced by the economic system run financial institutions in a country, both developing countries and developed countries. Today the trends of the economy financial institutions are divided into two systems, which attract the attention of the world, such as conventional and syariah (Islamic). Both of these banking practices have different financial principles, where these differences can affect the performance of the financial and banking assets themselves. This study aims to determine the differences in the financial performance of Bank MuamalatIndonesia and Commonwealth Bank of Indonesia, which is a bank with assets that are considered good productivity and be able to withstand certain economic conditions. This study using Economic Value Added (EVA) Method to measure how efficiently both of bank uses capital. The way to calculate EVA using NOPAT, that used to eliminate the possibility of diversion of funds (financial) in the company with a series of calculating NOPAT, IC, WACC, CC and EVA. This type of research is descriptive qualitative. The data was used as the source of both the bank's financial report in the period 2010- 2012. The study shows the financial performance of Bank Muamalat Indonesia better than the Commonwealth Bank of Indonesia, it can be seen from the results of Mumalat Bank Indonesia EVA, which shows an increasing trend and relative stable during the period 2010-2012 . While the Commonwealth Bank of Indonesia financial result showed a decreasing trend in 2010-2011 and in 2011-2012 only then stable.   Key words: Economic Value Added, EVA, Financial Report.